2019
DOI: 10.15628/holos.2019.8190
|View full text |Cite
|
Sign up to set email alerts
|

Critical Success Factors in the Implementation of Information Systems From the Perception of Users: A Public Sector Experience

Abstract: The objective of the article is to identify the perception of users of the Decision Support System (DSS), used by the Federal University of Brazil (UNIVASF), about the management of the Critical Success Factors (CSF) in the implementation of the Information System. The research, descriptive and quantitative, had data collected through a structured questionnaire, applied to Decision Support System users of the Federal University. The results reveal that organizational factors were perceived as those that receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…These studies have demonstrated the positive effects of system and information quality on user satisfaction [19][20][21]. Other ones have shown that individual factors, such as perceived usefulness and ease of use, influence user satisfaction [7,29]. Indeed, [30] found that user perception and perceived usefulness is a significant determinants of end-user satisfaction, which assists in the maximum utilization of the ERP system.…”
Section: Theoretical Gap and Hypothesis Proposalmentioning
confidence: 98%
See 2 more Smart Citations
“…These studies have demonstrated the positive effects of system and information quality on user satisfaction [19][20][21]. Other ones have shown that individual factors, such as perceived usefulness and ease of use, influence user satisfaction [7,29]. Indeed, [30] found that user perception and perceived usefulness is a significant determinants of end-user satisfaction, which assists in the maximum utilization of the ERP system.…”
Section: Theoretical Gap and Hypothesis Proposalmentioning
confidence: 98%
“…The results showed that senior management support, training, and system quality are predictors of user satisfaction [22] analyzed the influence of the work position and educational level of users on their satisfaction with the ERP system. They found that users' years of education and position are directly related to their satisfaction with this type of system [7] and found that organizational factors were most effectively managed when the highest rate of positive perception was obtained; however, preventive, corrective measures were neither adequate nor sufficient, obtaining the least positive perception.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation